(untitled) (Research, Society and Development, 2021)
The article analyzes, from an ethnography developed in Brazil, how actions involved in the preparation and commercialization of street food, permeated by Food and Nutrition Security, fall into the daily struggle of street vendors to guarantee family health and survival. The study took place in Recôncavo da Bahia. The field phase lasted seven months, when information was produced, using techniques such as systematic and participant observation and interviews with street vendors. Alternative sources, such as reports from local websites and newspapers, also composed research data. The analysis of the empirical material was based on theorists like Sennett and Antunes, to make understandings about the phenomenon. It was found that street food vendors develop complex practices, combining hard work, specific knowledge, culinary techniques, craftsmanship and social engagement of craftsmen, combined with the family’s productive force, which permeate the elaboration of food in the perspective of seeking guarantee SAN. Family networks made up mainly of black women, elderly people, among other bodies apparently excluded by the formal sector, who perform work with low monetary income and with high demand over their lifetime, depriving them of adequate access to health and conditions isonomic characteristics of SAN. These street vendors add up to a list of invisible workers, unprotected in terms of public policies aimed at the sector and subjected to a precarious work process. The perpetuation of a global problem is revealed: families immerse themselves in informality to survive, build strategies to adapt to the rules and negotiate the public space, however, they promote a ’pathologization of life’ to maintain their ’enterprises’.